Methane Production Pathway Regulated Proximally by Substrate Availability and Distally by Temperature in a High‐Latitude Mire Complex. Issue 10 (24th October 2019) - Chang, Kuang‐Yu; Riley, William J.; Brodie, Eoin L.; McCalley, Carmody K.; Crill, Patrick M.; Grant, Robert F.
Abstract: Projected 21st century changes in high‐latitude climate are expected to have significant impacts on permafrost thaw, which could cause substantial increases in emissions to the atmosphere of carbon dioxide (CO2 ) and methane (CH4, which has a global warming potential 28 times larger than CO2 over a 100‐year horizon). However, predicted CH4 emission rates are very uncertain due to difficulties in modeling complex interactions among hydrological, thermal, biogeochemical, and plant processes. Methanogenic production pathways (i.e., acetoclastic [AM] and hydrogenotrophic [HM]) and the magnitude of CH4 emissions may both change as permafrost thaws, but a mechanistic analysis of controls on such shifts in CH4 dynamics is lacking. In this study, we reproduced observed shifts in CH4 emissions and production pathways with a comprehensive biogeochemical model (ecosys) at the Stordalen Mire in subarctic Sweden. Our results demonstrate that soil temperature changes differently affect AM and HM substrate availability, which regulates magnitudes of AM, HM, and thereby net CH4 emissions. We predict very large landscape‐scale, vertical, and temporal variations in the modeled HM fraction, highlighting that measurement strategies for metrics that compare CH4 production pathways could benefit from model informed scale of temporal and spatial variance. Finally, our findings suggest that the warming and wetting trends projected in northern peatlands could enhance peatland AM fraction and CH4 emissions even without further permafrost degradation. Plain Language Summary: Permafrost peatlands store large amounts of carbon potentially vulnerable to decomposition, and the changing climate is expected to have significant and uncertain impacts on high‐latitude methane (CH4 ) emissions. CH4 is an important greenhouse gas, and CH4 emissions represent a positive feedback with climate change. In this study, we reproduced the observed shifts in CH4 dynamics with a comprehensive biogeochemical model (ecosys) at the Stordalen Mire in subarctic Sweden, and quantified the effects of individual factors that regulate CH4 dynamics. Our results show that CH4 production rates depend on soil temperature, which itself is affected by a series of hydrological and thermal feedbacks. In addition, our results indicate that changes in soil temperature could indirectly (via substrate production) induce the measured shifts in CH4 production pathways. Our findings suggest that the warming and wetting trends projected in high‐latitude regions could enhance peatland CH4 production rates, which could accelerate projected climate changes even without further permafrost degradation. Key Points: Changing soil temperatures differently affect substrates for acetoclastic (AM) and hydrogenotrophic (HM) methanogenesis Landscape changes from thawing permafrost lead to biogeophysical changes that contribute to increased methane emissions and AM fraction Large spatial and temporal variations in HM fraction are modeled, highlighting the uncertainty of single point measurements